One‐year safety and efficacy of ustekinumab and results of dose adjustment after switching from inadequate methotrexate treatment: the TRANSIT randomized trial in moderate‐to‐severe plaque psoriasis. (1st February 2014) - Reich, K.; Puig, L.; Paul, C.; Kragballe, K.; Luger, T.; Lambert, J.; Chimenti, S.; Girolomoni, G.; Nicolas, J.‐F.; Rizova, E.; Brunori, M.; Mistry, S.; et al.
Summary: Background: There are limited long‐term, 'real‐world' data on ustekinumab, or the effect of dose adjustment in suboptimal responders. Objectives: We describe 52‐week data from TRANSIT, which initiated ustekinumab by licensed regimen and investigated exploratory dose adjustment. Methods: Patients with moderate‐to‐severe psoriasis and inadequate methotrexate response received ustekinumab, with immediate or gradual methotrexate withdrawal. Outcomes were similar between treatment arms at week 12 (primary endpoint), so week 52 data were pooled. Patients weighing ≤ 100 kg or > 100 kg were administered ustekinumab 45 or 90 mg, respectively. Patients weighing ≤ 100 kg without 75% improvement in Psoriasis Area and Severity Index (PASI 75) response at weeks 28 or 40 received a dose adjustment to 90 mg. The primary analysis used observed data. Results: Overall, 391 and 98 patients received ustekinumab 45 and 90 mg, respectively. Forty‐four patients (9%) discontinued before week 52 (0·4% due to adverse events). At week 52 (in the overall population), 369 patients (83%) achieved a PASI score ≤ 5, and 341 patients (77%) achieved PASI 75; the median PASI score decreased from 15 at baseline to 1·8. At weeks 28 and 40, 84 and 31 patients, respectively, did not achieve PASI 75 and received a dose adjustment; by week 52, 35/82 (43%) and 15/31 (48%) of these patients, respectively, achieved PASI 75 (two discontinued between weeks 28 and 40). Conclusions: Ustekinumab showed sustained 1‐year efficacy and was well tolerated when initially administered according to label. Adjusting the ustekinumab dose to 90 mg may result in clinically meaningful improvement in response in patients weighing ≤ 100 kg with suboptimal initial response.